(untitled) (European Journal of Engineering Science and Technology, 2020)
The purpose of this work is to study the effect of concentration and temperature of agar agar solution on the rheological behavior of a complex fluid (agar agar solution) used on a capillary rheometer. The rheological properties of agar solution were studied, in particular the concentration’s effect (0.1%, 0.15%, 0.17% and 0.2%), and temperature (20°C, 30°C, 40°C, 50°C, 60°C and 70 °C) on the rheological behaviour of the agar agar solution. A comparative study of various rheological laws (Herschel-Buckley, Cross, Oswald De Waele, Bingham) was made, to etablish a model that presents the rheological behavior which applies to different samples of agar agar solution, based on the coefficient of correlation. Results indicated that the rheological behavior of agar agar solution depends on the range of shear rate used : for low shear rate (lower than 6.2 s-1) the solution of agar agar can be modeled by an Ostwald-De Waele-type power-law, but for the high shear rate (higher than 6.2 s-1) the solution of agar agar can be described by Bingham’s model. The concentration’s and temperature’s effect of agar agar solution on the two models studies’s parameters (Ostwald-De Waele, Bingham) was studied.We observe a decrease of consistency index ’k’ as a function of temperature, this decrease is more accentuated for temperatures ranging from 20 to 40 °C. On the other hand, above 40°C the decrease in the consistency index with temperature is less sensitive. The consistency index increases a function of concentration. the increase in the concentration of agar agar has a positive effect on the critical stress and plastic viscosity and the critical constraint ?_c and plastic viscosity ?p at high shear rates, decrease with increasing temperature.